Chuyển đổi số trong công tác quản lí đào tạo: Nghiên cứu tại Trường Cao đẳng Lý Tự Trọng Thành phố Hồ Chí Minh - Đinh , Văn Đệ; Phạm , Hữu Lộc; Nguyễn , Kính; Lương , Xuân Thịnh; Nguyễn , Thành Nam (Tạp chí Giáo dục, 2023)
Digital transformation is an inevitable trend of the time. As an educational innovation fueled by the explosion of electronic cloud, artificial intelligence (AI) and Internet of Things (IoT), providing transparent new ways and optimal service for education. Digital transformation in education will build many modern educational methods; under the support of information technology, changing traditional educational activities with software, simulation technology in teaching, etc. On the basis of technology 4.0, Vietnamese education will successfully connect with world education. This article studies digital transformation in training management: remarkable results at Ly Tu Trong College in Ho Chi Minh City. This research contributes to helping schools promote their strengths and overcome their weaknesses in the digital transformation process.